Inter-relationship between Malaysian and selected stock markets in the Far East and New York: parametric versus nonparametric approach revisited - Othman Yong, (Penerbit Universiti Kebangsaan Malaysia, 1993)
Most of the past studies suggested that considerable gains were available to investors who diversify their Investment portfolio lnternationally due to the usually low positive or negative correlations among world's stock markets. This study looks at the issue of stock market co-movement from a nonparametric approach as well as the commonly used parametrrc approach. This study uses daily and weekly indices of the markets of Malaysia, Hong Kong, Australia, Japan, and the United States for a period from January 1984 to December 1988. In general, the results of both techniques are not totally in agreement with each other However, both techniques suggest that the comovements among these markets are not stable with time which means that it is difficult to construct an optimal investment strategy based on the comovements.